The Effect of Self Talk Therapy on Anxiety in Hypertension Patients in Banyuraden, Yogyakarta - Rekha Amelia Putri; Wittin Khairani; Sarka Ade Susana (Jurnal Kesehatan Manarang, 2024)
Background: The phenomenon that occurs in hypertensive patients who are undergoing routine treatment or therapy, most sufferers feel anxious because of the treatment process, so patients need an effective problem-solving or coping mechanism to be able to reduce or overcome anxiety. There are several psychological interventions used to reduce anxiety, one of which is cognitive intervention. Self talk therapy is a cognitive way of working that contributes to changing negative thoughts into positive ones. Objective: Aims to determine the effect of self talk therapy on anxiety in hypertensive patients in Kalurahan Banyuraden, Gamping, Sleman, Yogyakarta. Method: This research is Pre-experiment design with One group Pretest-Posttest Design research design. This research will be conducted in April 2023. The sample in this study amounted to 90 respondents. Data analysis used Wilcoxon's non-parametric statistical test to see the difference between pretest and posttest in determining intervention results. Results: Results showed that there was a decrease in anxiety level scores experienced by 90 participants, where anxiety scores were in the moderate category. The results of data analysis showed that the value of Z = -8.248 with significance p = 0.000 (p< 0.05). Conclusion: There were significant changes in the score obtained by people with hypertension before and after the intervention. It is hoped that this intervention can help in reducing anxiety and can be done independently by people with hypertension.